Pelatihan Perawatan Kaki dan Self-Monitoring untuk Mencegah Ulkus Kaki Diabetikum Secara Mandiri - puspawati, dewi (Bakti Cendana, 2024)
Diabetes Mellitus is a non-communicable disease with a high prevalence globally, especially in developing countries, including Indonesia. One of the complications that often occurs is diabetic foot ulcers. These complications can be prevented early by involving elements in the community starting from patients, families, peer groups, cadres, community leaders and health workers. Based on this, the team conducted community service in the working area of the Sukawati II Health Center which aims to improve the ability of patients, families, elderly groups and health cadres to perform foot care and self-monitoring of foot health as an effort to prevent diabetic foot ulcers. The method used is counseling and simulation of foot examination and foot care. The activity was attended by 51 participants consisting of 15 DM patients, 13 patient families, 11 health cadres and 12 elderly people. The evaluation was carried out after the demonstration from the team, the participants were asked to re-simulate how to do foot care. Monitoring is carried out regularly every month for 2 months. The results showed that most of the participants (80%) were able to carry out foot care and self-monitoring at home and did not develop diabetic ulcers during the monitoring period.